Laminar distribution of the pathological changes in sporadic frontotemporal lobar degeneration with transactive response (TAR) DNA‐binding protein of 43 kDa (TDP‐43) proteinopathy: a quantitative study using polynomial curve fitting. Issue 4 (25th April 2013) - Armstrong, R. A.; Hamilton, R. L.; Mackenzie, I. R. A.; Hedreen, J.; Cairns, N. J.
<x xml:space="preserve">Abstract</x> R. A. Armstrong, R. L. Hamilton, I. R. A. Mackenzie, J. Hedreen and N. J. Cairns (2013) Neuropathology and Applied Neurobiology39, 335–347 Laminar distribution of the pathological changes in sporadic frontotemporal lobar degeneration with transactive response (TAR) DNA‐binding protein of 43 kDa (TDP‐43) proteinopathy: a quantitative study using polynomial curve fitting Aims: Previous data suggest heterogeneity in laminar distribution of the pathology in the molecular disorder frontotemporal lobar degeneration (FTLD) with transactive response (TAR) DNA‐binding protein of 43 kDa (TDP‐43) proteinopathy (FTLD‐TDP). To study this heterogeneity, we quantified the changes in density across the cortical laminae of neuronal cytoplasmic inclusions, glial inclusions, neuronal intranuclear inclusions, dystrophic neurites, surviving neurones, abnormally enlarged neurones, and vacuoles in regions of the frontal and temporal lobe. Methods: Changes in density of histological features across cortical gyri were studied in 10 sporadic cases of FTLD‐TDP using quantitative methods and polynomial curve fitting. Results: Our data suggest that laminar neuropathology in sporadic FTLD‐TDP is highly variable. Most commonly, neuronal cytoplasmic inclusions, dystrophic neurites and vacuolation were abundant in the upper laminae and glial inclusions, neuronal intranuclear inclusions, abnormally enlarged neurones, and glial cell nuclei in the lower laminae. TDP‐43‐immunoreactive inclusions affected more of the cortical profile in longer duration cases; their distribution varied with disease subtype, but was unrelated to Braak tangle score. Different TDP‐43‐immunoreactive inclusions were not spatially correlated. Conclusions: Laminar distribution of pathological features in 10 sporadic cases of FTLD‐TDP is heterogeneous and may be accounted for, in part, by disease subtype and disease duration. In addition, the feedforward and feedback cortico‐cortical connections may be compromised in FTLD‐TDP.